SECURITY ARCHITECTURE ON WIRELESS NETWORK TRAFFIC HANDOFF : A REVIEW - Wibawa, Sigit (Department of Computer Engineering, Universitas Wiralodra, 2021)
This paper provides an overview of the wireless handoff process on wireless networks by investigating Authentication Protocol using EAP -AKA (Extensible Authentication Protocol) - Authentication and Key Agreement The EAP-AKA protocol was developed for LAN networks or mobile network devices, the authors found ineffective network procedures guaranteed that made the attacks MITM and DoS attacks may occur. In addition, we find the storage procedures and resource submissions not safe enough to withstand DoS attacks. Focusing on Both types of attacks, the authors are interested in existing security protocol methods and written by researchers, then perform Systematic Literature Review (SLR) by using international journals database ie from the IEEE organization with the use of wireless handoff attack keyword in the middle of the world and obtained some related journals which need further research to deepen the Systematic Literature review, by offering a structured, methodical, and meticulous approach to understanding the research trends of handoff security issues on wireless networks and mobile networks. The purpose of this research is to provide credible intellectual guidance for future researchers to help them identify areas in the study. Most SLR is limited to conference papers and journal articles published by IEEE from 2015 to 2021. This study reveals that the protocol, privacy and security of the handoff process are the least studied, while the operating problems, architecture, methods in the handoff process get much attention in the literature.